Abnormality of epiphyseal plate induced by selenium deficiency diet in two generation DA rats. Issue 8 (25th May 2015) - Min, Zixin; Zhao, Wenxiang; Zhong, Nannan; Guo, Yuanxu; Sun, Mengyao; Wang, Quancheng; Zhang, Rui; Yan, Jidong; Tian, Lifang; Zhang, Fujun; Han, Yan; Ning, Qilan; et al.
<x xml:space="preserve">Abstract</x> This study aimed to observe the effects of Se deficiency on epiphyseal plates of two generation DA rats fed with artificial total synthetic low Se diet. All F0 and F1 DA rats were fed with synthetic low Se diet (SeD group) and low Se diet supplied with Se (SeS group). The levels of selenium and enzyme activities of GPx were detected in plasma of the rats. General growth of bone and articular cartilage was measured macroscopically and microscopically. The epiphyseal plate of femur heads or tibia were obtained to histological and immunohistochemical examinations. The cartilage from left knee joints and femur heads was used to detect the gene expression of collagens, ADAMTSs and several selenoproteins by RT‐qPCR. Two generation SeD rats showed Se insufficiency status. The thicknesses of the femur and tibial epiphyseal plates in both F0 and F1 SeD rats were significantly less than that of SeS rats. In F1 generation, SeD rats showed much fewer proliferative chondrocyte layers than SeS ones. Importantly, two generation SeD rats both showed significantly more serious pathological changes of epiphyseal plates. In two generation rats, gene expressions of COL II, GPx1 and GPx4 were significantly down‐regulated in SeD rats than SeS ones; meanwhile ADAMTS‐4 showed an up‐regulated expression in cartilage. Dietary Se deficiency can apparently cause epiphyseal plate lesion and decrease cartilage type II collagen production and GPx1 activity in two generation DA rats fed with the artificial total synthesis low Se diet.